Decreased exploratory activity in a mouse model of 15q duplication syndrome; implications for disturbance of serotonin signaling. - Kota Tamada (Public Library of Science (PLoS), 2010)
Autism spectrum disorders (ASDs) have garnered significant attention as an important grouping of developmental brain disorders. Recent genomic studies have revealed that inherited or de novo copy number variations (CNVs) are significantly involved in the pathophysiology of ASDs. In a previous report from our laboratory, we generated mice with CNVs as a model of ASDs, with a duplicated mouse chromosome 7C that is orthologous to human chromosome 15q11-13. Behavioral analyses revealed paternally duplicated (patDp/+) mice displayed abnormal behaviors resembling the symptoms of ASDs. In the present study, we extended these findings by performing various behavioral tests with C57BL/6J patDp/+ mice, and comprehensively measuring brain monoamine levels with ex vivo high performance liquid chromatography. Compared with wild-type controls, patDp/+ mice exhibited decreased locomotor and exploratory activities in the open field test, Y-maze test, and fear-conditioning test. Furthermore, their decreased activity levels overcame increased appetite induced by 24 hours of food deprivation in the novelty suppressed feeding test. Serotonin levels in several brain regions of adult patDp/+ mice were lower than those of wild-type control, with no concurrent changes in brain levels of dopamine or norepinephrine. Moreover, analysis of monoamines in postnatal developmental stages demonstrated reduced brain levels of serotonin in young patDp/+ mice. These findings suggest that a disrupted brain serotonergic system, especially during postnatal development, may generate the phenotypes of patDp/+ mice.